Advances in Applied NanoBio-Technologies 2020
DOI: 10.47277/aanbt/1(1)9
|View full text |Cite
|
Sign up to set email alerts
|

The importance of silver nanoparticles in human life

Abstract: One nanomaterial that is having an early impact in health care product is nano-silver. Silver has been used for the treatment of medical ailments for over 100 years due to its natural antibacterial and antifungal properties. The nano silver particles typically measure 25nm. They have extremely large relatively surface area, increasing their contact with bacteria or fungi, and vastly improving its bactericidal and fungicidal effectiveness. The nano silver when in contact with bacteria and fungus will adversely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Nanotechnology has been playing an important role in different fields of biology and medicine including targeted drug delivery (Ghosh, Girigoswami, & Girigoswami, 2019;Girigoswami, Pallavi, & Girigoswami, 2020), imaging (Gowtham et al, 2022;Jagannathan, 2022), biosensing (Akhtar, Metkar, Girigoswami, & Girigoswami, 2017;Girigoswami, Ramalakshmi, Akhtar, Metkar, & Girigoswami, 2019;, theranostics (Agraharam, Saravanan, Girigoswami, & Girigoswami, 2022;Chatterjee et al, 2023;Haribabu, Girigoswami, Girigoswami, & Nano-Objects, 2021;, nanoformulation of nutraceuticals (Balasubramanian, Girigoswami, & Girigoswami, 2022, etc. Among them, silver and gold have shown their special applications in many cosmetic and skin care products including the role of silver in improving female hygiene products, such as sanitary towels and panty liners (Ahmadi, 2020;Sakthi Devi, Girigoswami, Siddharth, & Girigoswami, 2022;Salvioni et al, 2021). There have been recent improvements in the amalgamation of natural products and nanostructures to yield effective coatings for female intimate hygiene products to relieve pain and other associated discomforts.…”
Section: Nanotechnology-based Female Hygiene Productsmentioning
confidence: 99%
“…Nanotechnology has been playing an important role in different fields of biology and medicine including targeted drug delivery (Ghosh, Girigoswami, & Girigoswami, 2019;Girigoswami, Pallavi, & Girigoswami, 2020), imaging (Gowtham et al, 2022;Jagannathan, 2022), biosensing (Akhtar, Metkar, Girigoswami, & Girigoswami, 2017;Girigoswami, Ramalakshmi, Akhtar, Metkar, & Girigoswami, 2019;, theranostics (Agraharam, Saravanan, Girigoswami, & Girigoswami, 2022;Chatterjee et al, 2023;Haribabu, Girigoswami, Girigoswami, & Nano-Objects, 2021;, nanoformulation of nutraceuticals (Balasubramanian, Girigoswami, & Girigoswami, 2022, etc. Among them, silver and gold have shown their special applications in many cosmetic and skin care products including the role of silver in improving female hygiene products, such as sanitary towels and panty liners (Ahmadi, 2020;Sakthi Devi, Girigoswami, Siddharth, & Girigoswami, 2022;Salvioni et al, 2021). There have been recent improvements in the amalgamation of natural products and nanostructures to yield effective coatings for female intimate hygiene products to relieve pain and other associated discomforts.…”
Section: Nanotechnology-based Female Hygiene Productsmentioning
confidence: 99%
“…Plant extracts have helped in the synthesis processes for different types of metal nanoparticles, from noble metal (palladium, silver, platinum, gold) nanoparticles to those based on iron [1,5]. It has been reported that some of the nanomaterials of particular importance in human life are silver nanoparticles, especially since they are obtained by green methods, having the potential to be biocompatible and less toxic compared to those synthesized by traditional chemical methods [6].…”
Section: Introductionmentioning
confidence: 99%